Unraveling the role of cigarette use in neural cannabis cue reactivity in heavy cannabis users. (5th August 2020) - Kuhns, Lauren; Kroon, Emese; Filbey, Francesca; Cousijn, Janna
Abstract: Cue reactivity is an important biomarker of cannabis use disorder (CUD). Despite high rates of cigarette and cannabis co‐use, its role in cannabis cue reactivity remains unclear. Using a visual functional magnetic resonance imaging cue reactivity paradigm, we investigated interactive effects of cannabis and cigarette use on cannabis cue relative to cigarette and neutral cue reactivity in a priori regions of interest—the amygdala, striatum, anterior cingulate cortex (ACC), ventral tegmental area (VTA), and orbitofrontal cortex—and a whole‐brain analysis. In our sample of cannabis users and controls closely matched on cigarette use, significant interactions between cannabis and cigarette use status emerged in the amygdala, striatum, ACC, frontal pole, and inferior frontal gyrus. Cannabis‐only users showed heightened cue reactivity in the amygdala compared with nonusing controls. Co‐users did not show heightened cue reactivity compared with cigarette smoking controls, although cue‐induced VTA activity was positively correlated with grams per week of cannabis. Cigarette smoking controls showed unexpectedly heightened cue reactivity compared to co‐users and nonsmoking controls. These findings and the high prevalence of cannabis and cigarette co‐use underscore the importance of considering cigarette smoking status when investigating the role of cue reactivity in heavy cannabis use. Abstract : Heightened neural cue reactivity is considered a biomarker of substance use disorders. Cigarette co‐use is common among heavy cannabis users and it matters when investigating cannabis cue reactivity. Across several regions of interest, cannabis only users demonstrated significantly elevated heightened cue reactivity compared to non‐cigarette smoking controls, while cannabis and cigarette co‐users did not. Cigarette smokers in the control group showed unexpectedly heightened levels of cannabis cue reactivity compared to non‐smoking controls and heavy cannabis users.